Limit analysis for partial-joint-penetration weld T-joints with arbitrary loading angles. (15th June 2020) - Luo, Pengjun; Asada, Hayato; Tanaka, Tsuyoshi
Highlights: Limit analysis is performed for T-joints with partial-joint-penetration weld. Strength evaluation equations are derived and used to evaluate the strength of T-joint. Numerical analysis is used to validate the analytical results and good agreement is achieved. Loading angle effect on PJP weld T-joint is more significant than fillet weld T-joint. Abstract: In the present study, limit analysis is performed for T-joints with partial-joint-penetration (PJP) weld by taking advantage of the slip-line field theory and von Mises failure criterion. The strength evaluation equations are derived from the limit analysis and applied to evaluate the ultimate strength of T-joints. The results indicate that ultimate strengths of the longitudinal T-joints are in proportion to the weld throat thickness and independent of weld type. Whereas, the transverse fillet weld and PJP weld T-joints respectively show about 40% and 180% strength increase comparing with their longitudinal counterparts. In addition, the loading angle and material stress ratio effects on the ultimate strength of T-joint are observed depending on the weld types significantly. The finite element models that have been calibrated using the test results are applied to validate analytical results. Good agreements are achieved between the analytical and numerical results regarding the ultimate strengths and fracture angles, which reveals the feasibility and the capacity of the proposed strength equations in evaluating the mechanical behavior of T-joints with arbitrary weld geometries, loading angles, and material stress ratios.